Risk factors for tobacco dependence in adolescent smokers. Issue 3 (25th May 2006) - Karp, I; O'Loughlin, J; Hanley, J; Tyndale, R F; Paradis, G
Abstract : Objective: To study the incidence of conversion to tobacco dependence (TD) and the prevalence of the TD state in relation to several potential determinants in a sample of adolescent smokers. Methods: Questionnaires were administered every 3–4 months to document TD symptoms, amount of cigarette consumption, and depression symptoms in a prospective cohort of 1293 grade 7 students in a convenience sample of 10 schools. Results: Over 54 months of follow-up, 113 of 344 novice smokers converted to TD. The referent series for the analysis of incidence comprised 823 person-surveys. The prevalence series included 1673 person-surveys, contributed by 429 smokers. Conversion to TD and TD status were associated with the intensity of recent (that is, past 3-month) cigarette consumption (adjusted incidence rate ratio (aIRR) 1.63 (95% confidence interval (CI) 1.36 to 1.97) and adjusted prevalence odds ratio (aPOR) 1.35 (95% CI 1.23 to 2.48) per 100 cigarettes per month), slowest CYP2A6 activity (aIRR 4.19 (95% CI 1.38 to 12.76) and aPOR 2.30 (95% CI 1.29 to 4.09)), depression score (aIRR 1.61 (95% CI 1.17 to 2.21) and aPOR 1.47 (95% CI 1.22, 1.75) per 1-unit change). Additional determinants included, for conversion to TD, time since onset of cigarette use (aIRR 0.76 (95% CI 0.58 to 1.00) per year) and, for the TD state, positive TD status six months ago (aPOR 3.53 (95% CI 2.41 to 5.19)). Conclusions: TD risk in adolescents is associated with intensity of recent cigarette consumption, while the role of more distant cigarette consumption appears small; subjects with slow nicotine metabolism and those with more depression symptoms are at increased risk of becoming tobacco dependent. The risk of being tobacco dependent is considerably higher in subjects who had previously developed the TD state.